The Nexus of Economic Policy Uncertainty, Cash Holdings, and Investment: A Systematic Literature Review from an Agency Theory Perspective - Pradita, Nungki; Tandelilin, Eduardus; Setiyono, Bowo (Organizations and Markets in Emerging Economies, 2026)
This systematic literature review (SLR), integrated with bibliometric analysis, provides a comprehensive investigation into the impact of economic policy uncertainty (EPU) on corporate strategic decisions. While previous studies often discuss EPU impacts broadly, this review specifically synthesizes the interplay between EPU, corporate cash holdings, and investment efficiency through the lens of agency theory. Using the PRISMA framework, a total of 105 high-quality articles published in Scopus-indexed journals (2018–2025) were analyzed. The bibliometric findings reveal that 66.7% of the literature is published in Q1 journals, with Elsevier as the dominant publisher. However, a significant research gap exists regarding the underrepresentation of emerging economies, particularly in developing markets where policy uncertainty effects remain understudied. The qualitative synthesis reveals that EPU significantly influences precautionary cash holdings and suppresses investment efficiency, with agency conflicts acting as a critical moderating mechanism. This study contributes by proposing an integrated conceptual framework that links policy uncertainty to managerial behavior, providing a foundation for future research to explore mitigation strategies in diverse institutional contexts, particularly in developing markets.